2004
DOI: 10.1038/sj.onc.1207202
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the nuclear receptor coactivator AIB1 isoform AIB1-Δ3 on estrogenic ligands with different intrinsic activity

Abstract: The nuclear receptor coactivator amplified in breast cancer 1 (AIB1) and its more active isoform AIB1-D3 are overexpressed in breast cancer and preneoplastic breast tissue. However, the impact of these proteins on the transcriptional activity of natural estrogens or selective estrogen receptor modulators (SERMs) has not been determined. Here we show that AIB1-D3 causes a significant increase in the efficacy of 17b-estradiol at both estrogen receptor-a (ER-a) and ER-b in ovarian, breast and endometrial cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…This increase in transcription is most likely due to a relief of repression of the endogenous AIB1 in the COS-7 cells because we are able to detect endogenous AIB1 protein by Western blot (17). Previous studies from our group and others have suggested that the N-terminal region containing the bHLH and PAS A domains contains an inhibitory domain that represses activity in both the nucleus and cytoplasm (17,18,21,26,36). Our studies and those from Chen et al (36) have shown that the loss of the N-terminal region leads to potent coactivation of nuclear hormone receptor-mediated transcription.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This increase in transcription is most likely due to a relief of repression of the endogenous AIB1 in the COS-7 cells because we are able to detect endogenous AIB1 protein by Western blot (17). Previous studies from our group and others have suggested that the N-terminal region containing the bHLH and PAS A domains contains an inhibitory domain that represses activity in both the nucleus and cytoplasm (17,18,21,26,36). Our studies and those from Chen et al (36) have shown that the loss of the N-terminal region leads to potent coactivation of nuclear hormone receptor-mediated transcription.…”
Section: Discussionmentioning
confidence: 72%
“…AIB1-⌬4 mRNA expression was elevated in breast tumor tissue relative to normal breast tissue (17). It was also shown to increase the efficacy of estrogenic compounds and the agonist effects of the selective estrogen receptor modulator tamoxifen in breast and endometrial tumor cells (17,18). Overexpression of AIB1-⌬4 in mice leads to ductal ectasia in the mammary gland with an increased expression of proliferative markers such as proliferating cell nuclear antigen, phospho-histone H3, and cyclin D1 (19) as well as increased cross-talk with ER␣ 2 in epithelial and stromal responses (20).…”
mentioning
confidence: 99%
“…Furthermore, AIB1 is rate-limiting for estrogen-mediated growth of MCF-7 human breast cancer cells (14). AIB1 gene expression is up-regulated by selective ER modulators, such as tamoxifen (15) and the estrogenic activity of selective ER modulators, can be increased by AIB1 and an AIB1 isoform (16). However, emerging data suggest that the role of AIB1 is not restricted to nuclear receptor signaling.…”
Section: Introductionmentioning
confidence: 91%
“…Several mechanisms have been proposed to explain why tamoxifen may act as an antagonist in some tissues and act as an agonist in others, including cell-specific tamoxifen-induced changes in ERa conformation or modifications that alter the ability of ERa to interact with coactivators or corepressors, expression levels of coactivators or corepressors, or activity of other intracellular signaling pathways (Dutertre and Smith, 2000;Graham et al, 2000;McDonnell et al, 2002;Heldring et al, 2004;Jordan, 2004;Smith and O'Malley, 2004). The agonist activity of tamoxifen is increased when the coactivator AIB1/SRC-3 or its isoform AIB1-D3 is overexpressed (Reiter et al, 2004) and tamoxifen increases steady-state protein levels of SRC-1 and AIB1/SRC-3 (Lonard et al, 2004). Higher levels of AIB1 expression in human breast cancer have been associated with poorer outcome following tamoxifen therapy .…”
Section: Discussionmentioning
confidence: 99%